2012
DOI: 10.1123/mcj.16.4.493
|View full text |Cite
|
Sign up to set email alerts
|

Phase-Dependent Respiratory-Motor Interactions in Reaction Time Tasks During Rhythmic Voluntary Breathing

Abstract: The study investigated squeezing reaction time (RT) in response to a visual cue during rhythmic voluntary breathing at 0.6 Hz paced by a metronome, breath holding, or at rest in 13 healthy subjects. Rhythmic voluntary breathing slowed down RT, only in the expiratory phase with accompanied changes in the length of respiratory phases, while breath-holding reduced RT. The prolonged RT during voluntary expiratory phases and the absence of changes in RT during voluntary inspiratory phases are most likely related to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Breathing rhythm is also a powerful force in shaping and coordinating other motor patterns, from fine orofacial movements, e.g., sniffing, whisking in rodents, and speech in humans, to large‐scale movements such as running and swimming (Daley, Bramble, & Carrier, ; Kleinfeld, Deschenes, Wang, & Moore, ; Moore et al, ). Notably, such disparate functions as reaction times (Beh & Nix‐James, ; Li, Park, & Borg, ) and pupillary diameter (Borgdorff, ; Ohtsuka, Asakura, Kawasaki, & Sawa, ) are modulated by the breathing cycle.…”
Section: Introductionmentioning
confidence: 99%
“…Breathing rhythm is also a powerful force in shaping and coordinating other motor patterns, from fine orofacial movements, e.g., sniffing, whisking in rodents, and speech in humans, to large‐scale movements such as running and swimming (Daley, Bramble, & Carrier, ; Kleinfeld, Deschenes, Wang, & Moore, ; Moore et al, ). Notably, such disparate functions as reaction times (Beh & Nix‐James, ; Li, Park, & Borg, ) and pupillary diameter (Borgdorff, ; Ohtsuka, Asakura, Kawasaki, & Sawa, ) are modulated by the breathing cycle.…”
Section: Introductionmentioning
confidence: 99%
“…However, interactions between respiration and non-respiratory functions have been documented in humans and rodents. In humans, for example, phase-locking with respiration has been observed for visual signal detection (Flexman et al, 1974) eye movements (Rittweger and Pöpel, 1998; Rassler and Raabe, 2003), the temporal grouping of pianistic finger movements (Ebert et al, 2002), reaction time to visual (Li et al, 2012) and auditory (Gallego et al, 1991) stimuli, and grip-force (Li and Laskin, 2006). Rassler et al (1996) reported that response latency, tracking-precision and movement duration of finger movements made to track a visual target showed significant respiratory-phase-dependent differences and that the respiratory-phase-dependence differed between finger flexion and extension movements (Rassler, 2000).…”
mentioning
confidence: 99%
“…Influence by respiration on sensory perception has in part been substantiated through studies on visual and auditory signal detection, revealing that the threshold for signal detection of hard to perceive stimuli is higher during inspiration compared to expiration [54]. During controlled breathing, reaction times are significantly longer during expiration compared to inspiration [55]. Natural, involuntary breathing showed similar extension of reaction time during expiration [52].…”
Section: Perceptionsmentioning
confidence: 99%